Simultaneous realization of time and carrier-envelope phase synchronization for an ultra-intense few-cycle laser pulse coherent combining system - Guoli Zhang; Xiao Liang; Hao Xue; Xinglong Xie; Ping Zhu; Fucai Ding; Meizhi Sun; Linjun Li; Rashid Ul Haq; Ailin Guo; Xiangbing Zhu; Jianqiang Zhu (High Power Laser Science and Engineering)
Coherent combining of several low-energy few-cycle beams offers a reliable and feasible approach to producing few-cycle laser pulses with energies exceeding the multi-joule level. However, time synchronization and carrier-envelope phase difference (ΔCEP) between pulses significantly affect the temporal waveform and intensity of the combined pulse, requiring precise measurement and control. Here, we propose a concise optical method based on the phase retrieval of spectral interference and quadratic function symmetry axis fitting to simultaneously measure the time synchronization and ΔCEP between few-cycle pulses. The control precision of our coherent beam combining system can achieve a time delay stability within 42 as and ΔCEP measurement precision of 40 mrad, enabling a maximum combining efficiency of 98.5%. This method can effectively improve the performance and stability of coherent beam combining systems for few-cycle lasers, which will facilitate the obtaining of high-quality few-cycle lasers with high energy.